2013
DOI: 10.1259/dmfr.20130176
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of buccal marginal alveolar peri-implant and periodontal defects using a cone beam CT system with and without the application of metal artefact reduction mode

Abstract: Buccal peri-implant defects were more difficult to detect than buccal periodontal defects. No difference was found among CBCT images obtained with and without AR modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
1
18

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 25 publications
2
103
1
18
Order By: Relevance
“…Further studies should be conducted to compare different implant brands in assessing defect visibility around implants. A recent study 19 found that there was no difference in the detection of simulated buccal peri-implant defects among CBCT images obtained with and without the artefact reduction modes of the Planmeca ProMax ® 3D Max CBCT unit (Planmeca Oy, Helsinki, Finland). In this study, we did not use any artefact reduction filter as the CBCT unit chosen for this study does not offer different artefact reduction modes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies should be conducted to compare different implant brands in assessing defect visibility around implants. A recent study 19 found that there was no difference in the detection of simulated buccal peri-implant defects among CBCT images obtained with and without the artefact reduction modes of the Planmeca ProMax ® 3D Max CBCT unit (Planmeca Oy, Helsinki, Finland). In this study, we did not use any artefact reduction filter as the CBCT unit chosen for this study does not offer different artefact reduction modes.…”
Section: Discussionmentioning
confidence: 99%
“…Streak artefacts due to the presence of scatter radiation as linear hyperdensities radiating from the metallic object might extend to the entire width of the field, affecting even the visualization of areas on the opposite side of the jaw. 15,19 Beam hardening artefacts appear as dark voids adjacent to high-density structures, such as titanium implants, and are due to the differential absorption of low-energy X-ray photons by high-density materials. 19,20 The severity of these artefacts produced by dental implants on image quality has been reported to be greater for CBCT than for multislice CT, 21 to be CBCT unit dependent, 22 to influence the reliability of linear measurements of adjacent marginal bone 23 and to vary depending on the implant surface, with increasing Gray values occurring on buccal and lingual aspects.…”
Section: Introductionmentioning
confidence: 99%
“…However, we could not confirm this hypothesis, as some have already reported. 4,24 When assessing two different imaging systems with AR (Picasso Master 3D and Planmeca ProMax ® 3D Max; Planmeca Oy, Helsinki, Finland) regarding root fracture diagnosis in teeth filled with gutta percha, Bechara et al 4 reported overall inferior results with the use of the tool. By using an AR in an attempt to improve the detection of peri-implant and periodontal defects, Kamburoglu et al 24 were also unable to deliver promising conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…4 Additionally, no differences were observed in the detection of simulated periodontal and peri-implant vestibular defects with or without the use of an AR. 24 Thus, the benefits of using an AR are not well established, and studies to date have used either subjective or objective evaluations but not the two forms of assessments combined. In addition, studies that evaluate the usefulness of AR in the detection of root fractures in teeth with intracanal metal posts, which happen relatively often, are missing.…”
Section: Introductionmentioning
confidence: 99%
“…Um deles foi realizado por Kamburoglu et al, (19 A região anterior apresentou uma espessura média de 0,9 mm de tábua óssea vestibular, e essa aumentou quanto mais posterior era o dente. Uma alta frequência de deiscências foram encontradas na região anterior e posterior, respectivamente (9,9% a 51,6% e 3,1% a 53,6%).…”
Section: Tomografia Computadorizada De Feixe Cônico (Tcfc) E Artefatounclassified